(untitled) (Research, Society and Development, 2022)
Hematopoietic Cell Transplantation (HCT) is a procedure that aims to achieve restoration of patients with hematological diseases. Hemorrhagic Cystitis (HC) is one of the complications of HCT and its incidence varies from 10% to 60% of transplanted cases, characterized as a hemorrhagic inflammatory process of the bladder mucosa and can occur in 4 degrees of intensity. Studies show that there is a relationship between the use of chemotherapeutic drugs, especially cyclophosphamide with urotropic viruses, such as polyomavirus (BKV and JCV), adenovirus (ADV) and cytomegalovirus (CMV). Methods of treatment and prophylaxis can be by stopping or reducing drugs, as well as hyperhydration, continuous bladder irrigation by alum and/or formalin, as well as viral therapy with the use of cidofovir. There is a high rate of patients affected by this complication, thus, the aim of this paper is a literature review, with the inclusion criteria being articles that describe the incidence and the pharmacotherapeutic methods used, and those in which the patients do not fit these characteristics will be excluded from the study. Based on the data, it is concluded that CH has a great importance in public health, due to its high rate of morbidity and mortality in patients after CHT. Still, late and/or early CH needs more attention to the patient in an individual and independent evaluation.